Integrated STEM for sustainability in school and early teacher education: a systematic review (2019–2025) - Kopbossyn, Amandyk; Laiskhanov, Shakhislam; Aksoy, Bülent; Tokbergenova, Aigul; Nametkulov, Mukhit; Kozybakova, Assel (Frontiers in Education, 2025)
This systematic review synthesizes research on school-focused initiatives that integrate science, technology, engineering, and mathematics (STEM) with sustainability goals, published between 2019 and 2025. Searches of Scopus, Web of Science, and SpringerLink, along with reference checks, identified 49 studies. We coded approaches, topics, technology use, outcomes, and implementation features. Of these 19 studies, 42 empirical interventions were mapped by topic and subject, while seven conceptual or non-anchored pieces were excluded from topic counts but were used for informed interpretation. Publications accelerated after 2020 and clustered in North America and Southeast/East Asia. Climate dominated the topic distributions, followed by water and circularity; biodiversity and energy were at moderate levels, while smaller clusters addressed disaster, built environment, and justice/policy. Technology integration was most prevalent in water and circularity units, moderate in disaster and built environment, and comparatively limited in climate; energy and justice/policy showed minimal technology integration. Outcome synthesis indicated broad gains from project-based and inquiry-oriented designs and from context/place-based approaches; socio-scientific argumentation most consistently advanced agency and values; modeling and engineering design excelled on skills and, with coherence supports, also improved concepts. A synthesized framework addresses key implementation challenges—curriculum fit, teacher capacity, cognitive load, assessment alignment, and equity logistics. The review offers design-ready guidance for selecting approaches that match desired learning and participation outcomes.